PEDAGOGIC STUDIES IN EFFORTS TO IMPROVE TEACHER TEACHING PERFORMANCE - Abadi, Rido Yusuf; Triatna, Cepi; Nurdin, Nurdin (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
This article aims to discover and explain the relationship between pedagogical studies and teachers’ teaching performance, which can be reflected in students’ learning outcomes. This article can be helpful and add insight into pedagogical studies' role in improving teacher teaching performance. In writing this article, the researchers used a method that can be referred to as library research. In this library research, the researchers used the media to collect library materials, such as books, journals, articles, and the like, to support this research in solving problems. The result is that pedagogic studies, in this case, pedagogic competencies, are very important for a teacher because they can help improve a teacher’s performance. Pedagogic studies and a teacher’s teaching performance have a proportional relationship; the better the teacher's ability/competence in pedagogic studies, the better the teacher's teaching performance is. Pedagogic Competence is a fundamental ability that teachers must possess and has an essential influence on Indonesian education. This is because pedagogically competent teachers must determine the success and failure of a learning process that will affect students' future.